Assessing Potential Intermediate Host Snails of Urogenital Schistosomiasis, Human Water Contact Behavior and Water Physico-chemical Characteristics in Alwero Dam Reservoir, Ethiopia. (September 2022) - Deribew, Ketema; Erko, Berhanu; Tiku Mereta, Seid; Yewhalaw, Delenasaw; Mekonnen, Zeleke
Introduction: Urogenital schistosomiasis is one of public health problems in lowland areas of Ethiopia. The disease is caused by Schistosoma haematobium . Freshwater Bulinus snails are intermediate hosts for the parasite transmission. The aim of the study was to assess intermediate host snails of urogenital schistosomiasis, human water contact behavior and physico-chemical characteristics of Alwero Dam reservoir. Methods: Bulinus snails were sampled from 12 sites of Alwero Dam. Bulinus snails were collected, identified and examined for natural schistosome infections. A total of 206 people were interviewed to determine human water contact behavior. The water temperature, pH, dissolved oxygen, total dissolved solid, salinity and conductivity of the water were determined. Results: Of 1125 Bulinus snails collected, 72 (6.4%) were infected with echinostome cercariae but none of them were infected with schistosome cercariae. The abundance of Bulinus species did not show significant variation across seasons ( P  = .61). Occurrence of Bulinus species was significantly higher in stony substratum than sandy substratum ( P  = .01). Of the total 206 participants, 119 (57.8%) had water contact activities like washing clothes, bathing or swimming. Majority of respondents (70.0%) reported that they visited the dam reservoir once or twice a week, while 16.5% and 13.6% reported that they visited the dam 3 to 5 times a week and daily, respectively. Moreover, 72.3% of the respondents had reported they had history of urogenital schistosomiasis infection. The mean water temperature, pH, dissolved oxygen, total dissolved solid, electric conductivity, and salinity of the dam water was 28.6°C, 7.07, 5.75 mg/l, 90.0 ppm, 124.8 µS/cm, and 50.0 ppm, respectively. Conclusion: At Alwero Dam, Bulinus snails were highly abundant and the human water contact activities were frequent. Therefore, the community awareness creation should be made to reduce water contact with snail infested water to prevent risk of urogenital schistosomiasis infection.